O estado brasileiro: transformações sob a égide da financeirização - Ferreira, Mariana Ribeiro Jansen (2007)
The aim of this study is to analyze how the financial supremacy modified the way that the State acts in the Brazilian economy. With this purpose, initially is characterize the financial supremacy and understood how this is part of the own logic of the capital, using the Marxist concept, in which the financial capital is the most perfect form of the capital, apparently with the financial capital disengaged in relation with the productivity range. This way, the financial supremacy can be characterize by the own necessity of capital reproduction, that after strong accumulation in the decades of 60´s and 70´s demands new ways to reproduce itself. This stimulated a growing diversification of financial instruments, the emerging of new agents with the ability of concentrate capital, deregulation, liberalisation, and changes in the financial intermediation on the markets, besides the financial and commercial globalization. The Latin- American countries became part of this movement through the reception of capital flows, that were sent toward those countries considering the excess of international liquidity and the own necessity of reproduction of the capital, and form a huge public debt. This phase of capitalism produced deep changes in the National States action and in Latin America that was felt through the adoption of the neo-liberalism. In Brazil, those changes occurred together with the crises of the State that previously had a very strong participation in the economy and that could not deal with the priorities of the elite that were now align with the movements of the national and international financial capital. This way, it is analyze the adoption of the neoliberalism and the measures that came together with it as privatization, financial and commercial opening and the used of liberal economic policies. The financial supremacy of the economy deeply changed the State intervention previously more attached with productive gains and that now stand back from the direct intervention in the economic growth. Those changes can be clearly seen through the evolution of the State budget execution that previously spend a lot in investments and in activities connect with the national development, as in industry, services and commerce, energy, transport and during the 90´s and 00´s reduced the expenses on those and increase the expenses attached with the financial market, as the payment of interest and redemption of the public debt. Analyzing the budget execution through charges group or functions shows this same shift. This way, the financial supremacy guide on the beginning of this XXI century the priorities on expense and all sort of policies made by the Brazilian National State